Despair [videorecording (DVD)] - Fassbinder, Rainer Werner, 1945-1982; Bogarde, Dirk, 1921-1999; Ferréol, Andréa, 1947-; Löwitsch, Klaus, 1936-2002; Spengler, Volker; Wicki, Bernhard, 1919-2000; Stoppard, Tom; Nabokov, Vladimir Vladimirovich, 1899-1977 (Olive Films, 2011)
Hermann Hermann, a Russian emigrant and successful chocolate magnate, starts to experience hallucinations. One day, he meets Felix and is sure that this man is his doppelganger. His delusional thinking leads him to hatch a plan to relieve him of his mental anguish.